Non‐native pink salmon Oncorhynchus gorbuscha carcasses benefit native benthic macroinvertebrates - Hui Wei; Gordon H. Copp; Rasmus B. Lauridsen; Tea Bašić; Phil I. Davison; John F. Murphy; James L. Pretty; Michał E. Skóra; Gabriela Zemelka; John Iwan Jones (Journal of Fish Biology, 2026)
The invasion of the North Atlantic by pink salmon Oncorhynchus gorbuscha has raised concerns regarding their impact on coastal rivers. Although the influence of marine‐derived nutrients from returning adult O. gorbuscha on rivers in their native range has received much attention, the ecological consequences of invasive O. gorbuscha for ecosystems outside the native range are largely unknown. To investigate the impact on the density and community structure of benthic macroinvertebrates, O. gorbuscha carcasses were added to 12 experimental channels for 60 days at three treatment levels (control, no carcass; low and high, loading rates). Stable isotopes of carbon (δ 13 C) and nitrogen (δ 15 N) were used to determine if nutrients from carcasses were incorporated into native biota. The density of macroinvertebrates increased close to the carcasses in the high‐addition treatment, suggesting aggregation. Furthermore, macroinvertebrates had a higher δ 15 N near to the carcasses in the low‐ and high‐addition treatments after 30 days, indicating uptake from the carcasses. The higher δ 15 N of willow moss Fontinalis antipyretica in carcass‐addition treatments indicated that primary producers could also assimilate nutrients from the decomposition of carcasses. Whilst the addition of carcasses resulted in the increased density of small individuals of macroinvertebrates, this did not propagate to changes in community composition in this relatively short experiment. Overall, the results suggest that native biota might benefit from the marine‐derived nutrients transported to streams by invasive O. gorbuscha , however, the long‐term effects of such nutrient/energy subsidies on receiving ecosystems require further investigation.